Financial Services and Preferential Trade Agreements : Lessons from Latin America - Haddad, Mona; Stephanou, Constantinos (World Bank, 2012)
This book deals with financial liberalization issues in the context of trade negotiations. The liberalization of trade and investment in financial services is only a subset of the broader financial liberalization agenda. The purpose of trade and investment liberalization is to increase financial market access and remove discriminatory and other access-impeding barriers to foreign competition. By contrast, the main purpose of financial liberalization is to remove distortions in domestic financial systems that impede competition and the allocation of capital to its most productive and profitable uses. In turn, financial liberalization can be divided into domestic financial reform and capital account opening, and there is a rich literature on its appropriate speed and sequencing. The first part of the book covers the fundamental principles that affect trade liberalization in financial services at both the multilateral and the regional levels. It analyzes the various models of preferential trade agreements (PTAs) used by negotiators and the architectural differences of these models. The second part of this book provides concrete examples of how countries have negotiated these agreements by focusing on the specific country experiences of Chile, Colombia, and Costa Rica. These case studies provide the reader with a thorough understanding of how countries strategize, negotiate, and implement regional trade agreements in financial services.